The Influence of Capital Adequacy Ratio and Governance on Financial Performance at PT. Bank Raya Indonesia Tbk - Warasto, Hestu Nugroho; Janudin, J. (Manunggal Halim Jaya, 2025)
This study aims to examine the influence of Capital Adequacy Ratio (CAR) and Good Corporate Governance (GCG), measured by the number of directors and independent commissioners, on the financial performance of PT Bank Raya Indonesia Tbk. Employing a quantitative approach with a descriptive-verificative method, the research uses secondary data from the bank's audited annual financial reports between 2017 and 2023. The population of this study comprises all bank published financial statements, while the sample is selected through purposive sampling based on data availability and completeness. Data were analyzed using multiple linear regression with SPSS software. The findings indicate that CAR and the number of directors significantly influence the bank's financial performance, while the number of independent commissioners does not show a significant effect. These results highlight the importance of capital strength and effective leadership structure in enhancing financial outcomes, providing valuable insights for banks undergoing digital transformation and facing increasing industry competition.